The impact of the climate crisis on economic, social, and cultural rights in Africa : Evaluating the African Charter on Human and Peoples' Rights - Kuveya, Lloyd (University of Pretoria, 2024)
Mini Dissertation (MPhil (Human Rights and Democratisation in Africa))--University of Pretoria, 2023.